Insights into liquid phase sintering mechanism of high-alumina and low-silica hematite ores - Wanlong Fan; Zhiwei Peng; Tuo Pan; Huibo Liu; Shaochang Nie; Lin Xiong; Qiang Zhong; Mingjun Rao (Minerals Engineering, 2026)

Dielectrically tuned core-shell microwave-responsive sorbents for high-efficiency direct air capture - Wenjing Li; Mingxing Zhou; Xiaoyan Ji; Yunxia Wen; Han Lin; Xiaohua Lu; Xinwei Zhang; Xiwen Zhang; Tuo Ji; Shuandi Hou; Jiahua Zhu (Chemical Engineering Journal, 2026)

Facile removal of alkali metals with production of potassium fertilizer from iron ore sintering baghouse dust - Tuo Pan; Zhiwei Peng; Shaochang Nie; Lin Xiong; Xiaoguang Bai; Jianzhi Zhang (Journal of Environmental Chemical Engineering, 2026)

Nicotinamide mononucleotide (NMN) improves the ovarian microenvironment associated with oocyte quality by increasing estrogen signaling, reprogramming ovarian metabolism, reducing oxidative stress, and inhibiting apoptosis in the spotted scat (Scatophagus argus) - Jie Luo; Siqin Wang; Xinghua Lin; Tuo Wang; Jinli Li; Dongneng Jiang; Tianli Wu; Siping Deng (Theriogenology, 2026)

Establishment of an efficient Agrobacterium-mediated transformation system and CRISPR/Cas9-mediated genome editing of the OvPDS1 gene in Oxalis vulcanicola ‘Sunset Velvet’ - Wanli Tuo; Xuexuan Wang; Tong Wu; Shentao Zhang; Pingting Guo; Xinyun Lin; Qianyu Lin; Junwen Zhai; Shasha Wu (Planta, 2026)

Differential responses of soil bacterial community and respiration to plastic film and straw mulching in a maize field - Xiaoqi Luo; Nanping Lin; Naijiang Wang; Benhua Sun; Yunfei Tuo; Jianqiang Li; Haixin Chen; Hao Feng (Biology and Fertility of Soils, 2026)

Microbial insights into a high water-quality dependent freshwater snail: Geographical origin and rearing mode shape the gut antibiotic resistance gene profile of Sulcospira hainanensis - Lingtong Ye; Chen Chen; Shengli Fu; Jie Lu; Tuo Yao; Huajian Lin; Zhifu Liang; Huan Li; Jinxia Peng; Zhenhua Ma (Environmental Pollution, 2026)

High-temperature assimilation behavior of steel slag tailings for iron ore sintering - Tuo Pan; Zhiwei Peng; Wanlong Fan; Huibo Liu; Qiang Zhong; Shaochang Nie; Lin Xiong (Process Safety and Environmental Protection, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

TgSclB1 orchestrates anti-oomycete activity by regulating mono-methyl phthalate biosynthesis in Trichoderma guizhouense - Yang Liu; Xiaoteng Shi; Tuokai Wang; Lvxun Tang; Yihao Zhou; Bozheng Lin; Linhua Cao; Siqiao Chen; Tuo Li; Dongyang Liu; Qirong Shen (Plant and Soil, 2026)

Intelligent recognition of the fermentation stage of baijiu based on multi-dimensional data fusion and interpretable machine learning - Lin Du; Junchao Zhou; Yongqing Tang; Xuan Liu; Jing Zhong; Bo Yang; Yuancheng He; Xianguo Tuo; Haiping Du (Food Research International, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

Associations between concurrent neonicotinoid, pyrethroid, and organophosphate insecticide metabolites and neurocognitive performance in Ecuadorian adolescents - Jessica Yen; Kun Yang; Tuo Lin; Xin M. Tu; Georgia Kayser; Rajendra P. Parajuli; Ana Skomal; Sheila Gahagan; Jose Suarez-Torres; Suzi Hong; Raeanne C. Moore; Jose R. Suarez-Lopez (Science of The Total Environment, 2025)

Concentration-dependent visual SO2 detection from trace to pure in a zirconium MOF - Guang-Rui Si; Xiang-Jing Kong; Lin-Hua Xie; You-Tuo Zhang; Tao He; Jian-Rong Li (Science Bulletin, 2025)

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

Unlocking the synergistic effects in biomass-plastic Co-pyrolysis using a hybrid machine learning approach with blended rule descriptors - Peng Jiang; Wenjie She; Hao Zhang; Lin Li; Han Lin; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Biomass and Bioenergy, 2025)

Dielectrically optimized Ni/CeO2/CNT catalysts for low-power and stable microwave-assisted dry reforming of methane - Tingting Wang; Xiaojun Li; Fengjuan Liu; Bei Liu; Xinkang Peng; Zhiheng Wang; Ning Qu; Jie Kong; Zhenchen Tang; Feng Zeng; Han Lin; Xiaohua Lu; et al. (Chemical Engineering Journal, 2025)

Rapid screening of inorganic arsenic in groundwater on-site by a portable three-channel colorimeter - Xiaobao Tuo; Yanhua Duan; Guanting Lin; Tianci Jiang; Wenhui Liu; Fangyi Chen; Xianjun Xie; Yan Zheng (Journal of Environmental Sciences, 2025)

A redox-modulating coating with multi-enzyme activity on engineered nanoparticles: An effective strategy for enhancing the control of plant bacterial diseases - Zhenghao Ding; Liwei Liu; Qingqing Song; Lin Chen; Guangdi Wang; Hong Li; Xinxin Tuo; Zhibing Wu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2025)

Study on dynamic changes in characteristic volatile compounds uncovers aroma development of Hainan Dayezhong (Camellia sinensis var. assamica) black tea - Yunfei Hu; Jialin Wang; Jun Tang; Ronghua Huang; Wenyuan Luo; Yanming Tuo; Ningkai Liao; Dawen Zhuang; Jinke Lin; Yue Zhang; Lei Pan; Liangyu Wu (Food Chemistry, 2025)

An Energy-Efficient Thrust Allocation Based on the Improved Dung Beetle Optimizer for the Dynamic Positioning System of Vessels - Yulong Tuo; Jianlong Lin; Zhouhua Peng; Yuanhui Wang; Shasha Wang (Journal of Marine Science and Engineering, 2025)
This paper investigates the constrained nonlinear thrust allocation problem for the dynamic positioning system of vessels. Considering the wear, energy consumption, and allocation error of thrusters, a constrained nonlinear mathematical optimization model of thrust allocation is established based on the “Hai Yang Shi You 201”. Based on the dung beetle optimizer (DBO) algorithm, a hybrid Osprey adaptive t-distribution DBO (HOATDBO) algorithm is presented to achieve the thrust allocation. The HOATDBO algorithm introduces the global exploration strategy of the Osprey algorithm, with the addition of the initialization of the good point set and adaptive t-distribution perturbations. The proposed HOATDBO algorithm has perfect global and local optimization capabilities, which can quickly and reliably obtain the optimal thrust solution, improve the thrust allocation accuracy of vessels, and reduce energy consumption. Finally, the simulation and comparison results are presented to verify the superiority of the proposed HOATDBO algorithm.

Urbanization induced Urban Canopy Parameters enhance the heatwave intensity: A case study of Beijing - Tuo Chen; Shirao Liu; Xuecao Li; Lin Pei; Mengqing Geng; Guojiang Yu; Zitong Shi; Tengyun Hu (Sustainable Cities and Society, 2025)

Integrating machine learning for multi-objective optimization of biomass conversion to hydrogen - Yinchen Li; Peng Jiang; Lin Li; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Journal of Cleaner Production, 2025)

Construction of diffusion and binding synergy in carbon-supported catalysts with varied Pd0/PdO Ratios for direct synthesis of hydrogen peroxide - Zhiheng Wang; Jiali Huang; Guancong Jiang; Tuo Ji; Han Lin; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Chemical Engineering Journal, 2025)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Study on metabolic variation reveals metabolites important for flavor development and antioxidant property of Hainan Dayezhong black tea - Yunfei Hu; Jialin Wang; Wenyuan Luo; Jun Tang; Yanming Tuo; Ningkai Liao; Dawen Zhuang; Kehang Yang; Jinke Lin; Yue Zhang; Liangyu Wu (Food Research International, 2024)

Networking SiO2-Al2O3 and amines into robust and long-lasting molded sorbents for continuous CO2 capture - Tong Zhou; Zhinan Wu; Yunxia Wen; Zhengxing Dai; Shuailong Song; Han Lin; Xin Feng; Xiaohua Lu; Tuo Ji; Jiahua Zhu (Chemical Engineering Journal, 2024)

Ozone exceedance forecasting with enhanced extreme instance augmentation: A case study in Germany - Tuo Deng; Astrid Manders; Arjo Segers; Arnold Willem Heemink; Hai Xiang Lin (Environmental Modelling & Software, 2024)

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Mechanism study of synergistic aluminum extraction and purification by ammonium for high-value conversion of secondary aluminum dross - Wen Deng; Qinglin Xie; Rui Zhou; Haorui Tuo; Xueming Liu; Hong Deng; Zhang Lin (Journal of Environmental Chemical Engineering, 2024)

The preparation of synbiotic AHY relieving loperamide-induced constipation and its modulation mechanism in vivo - Lai Jiang; Rui Zhang; Xudong Lin; Yanfeng Tuo; Guangqing Mu; Shujuan Jiang (Food Bioscience, 2024)

Causal Association of Cytokines and Growth Factors with Stroke and Its Subtypes: a Mendelian Randomization Study - Gengbin Chen; Tuo Lin; Manfeng Wu; Guiyuan Cai; Cheng Wu; Qian Ding; Jiayue Xu; Hongying Chen; Wanqi Li; Guangqing Xu; Yue Lan (Molecular Neurobiology, 2024)

Deciphering decadal observation of Fukushima-derived radiocesium in the most polluted port near the Fukushima Daiichi Nuclear Power Plant: from seawater to marine fish - Wuhui Lin; Yibang Zhang; Jinqiu Du; Jiliang Xuan; Fei Tuo (Frontiers in Marine Science, 2024)
The biological concentration effect of radionuclides in marine fish has exacerbated public anxiety about seafood security in the context of Fukushima nuclear-contaminated water discharged into the ocean. However, the most polluted port near the Fukushima Daiichi Nuclear Power Plant (FDNPP) has seldom been investigated, especially for radioactivity in marine fish. In this study, decadal observations of radiocesium in marine fish and seawater from the most polluted port were simultaneously established after the Fukushima Nuclear Accident. We found a generally decreasing trend of historical 137 Cs activity in seawater, with seasonal variations modulated by precipitation. Seasonal variations were elucidated with finer detail and divided into exponential decline in the dry season and steady variation in the wet season. A novel method was proposed to estimate the continuing source term of 137 Cs derived from the FDNPP, which was 3.9 PBq in 2011 and 19.3 TBq between 2012 and 2022 on the basis of historical 137 Cs. The biological concentration effect of marine fish is quantitatively emphasized according to the higher ratio of over-standards for radiocesium in marine fish relative to that in seawater. Long-term observation and analysis of radiocesium in marine fish and seawater from the most polluted port would provide insights into the scientific evaluation of the effectiveness of the decommissioning of the FDNPP in the past and share lessons on the fate of Fukushima-derived radionuclides in the future.

Characteristics and migration patterns of selenium in soil, crops, and hair within a typical alkaline arid agricultural region of Northwest China - Xiaoyan Ma; Wanshan Lei; Xin Lin; Xiangchuan Li; Shengfei Yang; Xiaohuang Liu; Tuo Liu (Journal of Geochemical Exploration, 2024)

Instability in a carbon pool driven by multiple dissolved organic matter sources in a eutrophic lake basin: Potential factors for increased greenhouse gas emissions - Jie Ma; Muchun Zhou; Yu Peng; Ya Tuo; Chuanqiao Zhou; Kexin Liu; Yilin Huang; Fei He; Qiuying Lai; Zhihui Zhang; Tsuyoshi Kinouchi; Shuyin Li; et al. (Journal of Environmental Management, 2024)

Screening and degradation characteristics of plastic-degrading microorganisms in film-mulched vegetable soil - Zhenyan Lin; Tuo Jin; Xin Xu; Xiao Yin; Dan Zhang; Mengjiao Geng; Chunyu Pang; Gongwen Luo; Lizhi Xiong; Jianwei Peng; Jiangchi Fei (International Biodeterioration & Biodegradation, 2024)

One-step synthesis of thiol-functionalized metal coordination polymers: effective and superfast removal of Hg (II) in the different matrices to ppb level - Mingzhi Li; Yongjie Tuo; Qiuxia Wu; Haiying Lin; Qingge Feng; Yu Duan; Junqi Wei; Zixuan Chen; Jiatong Lv; Lianghong Li (Chemosphere, 2023)

Interface interaction between silica and organic macromolecule conditioned forward osmosis membranes: Insights into quantitative thermodynamics and dynamics - Xianzheng Zhu; Tuo Tian; Danyang Li; Shengqiang Hei; Lu Chen; Guangqing Song; Weichen Lin; Xia Huang (Water Research, 2023)

Exploring the abundance and influencing factors of antimicrobial resistance genes in manure plasmidome from swine farms - Zunfang Tu; Junrui Shui; Jinxin Liu; Hongmei Tuo; Haoyu Zhang; Cong Lin; Jingyi Feng; Yuxuan Feng; Wen Su; Anyun Zhang (Journal of Environmental Sciences, 2023)

Kinetic insights into deoxygenation of vegetable oils to produce second-generation biodiesel - Dong Lin; Zhiwei Mao; Xiang Feng; Xin Zhou; Hao Yan; Huihong Zhu; Yibin Liu; Xiaobo Chen; Yongxiao Tuo; Chong Peng; De Chen; Chaohe Yang (Fuel, 2023)

Diversity and distribution of Perkinsus spp. along the coast of China: Implications for widespread transmission of Perkinsus spp. in mollusks - Lingtong Ye; Lin Wu; Jie Lu; Tuo Yao; Jiangyong Wang; Shaokun Shi; Gang Yu; Wang Zhao (Frontiers in Marine Science, 2022)
Perkinsus species, which are parasitic pathogens of mollusks, have been transmitted and dispersed to various molluscan species along the coastal waters of many countries. However, few studies have addressed the diversity and distribution of Perkinsus spp. along the coast of China. Here we used conventional PCR amplification and sequencing techniques, combined with a qPCR assay as a confirmatory test, to evaluate the prevalence of Perkinsus species in molluscan species among different sea regions of China. Three Perkinsus species —P. olseni , P. beihaiensis , and P. chesapeaki— were detected, with P. chesapeaki reported for the first time along the Chinese coast. Seven of eight molluscan species carried Perkinsus species, including Crassostrea gigas , C. hongkongensis , Sinonovacula constricta , Ruditapes philippinarum , Scapharca subcrenata , Meretrix lyrate , and Haliotis diversicolor . Perkinsus olseni was prominent in the Yellow and Bohai Sea and East China Sea, while P. beihaiensis was prominent in the South China Sea. Most of the molluscan species carried Perkinsus spp. with the medium or low levels of PCR-prevalence (<30%). The three Perkinsus species possess high levels of internal transcriber spacer haplotypes, some of which are shared among many countries. The much higher PCR-prevalence of Perkinsus spp. in the clam Ruditapes philippinarum and the oyster Crassostrea hongkongensis suggests that Perkinsus species may be transmitted and dispersed to other mollusks through the transportation of Perkinsus -carried R. philippinarum and C. hongkongensis . Perkinsus carrying tended to be generally linked with a broader geographic range, lower prevalence, more diversified molluscan hosts, and more diversified Perkinsus haplotypes.

Insights into the fates of plasmids and antimicrobial resistance genes during swine manure treatment and related factors based on plasmidome and metagenome analyses - Junrui Shui; Hongmei Tuo; Jinxin Liu; Xialan Zhang; Jingyi Feng; Yuxuan Feng; Wen Su; Cong Lin; Haoyu Zhang; Zunfang Tu; Hongning Wang; Anyun Zhang (Environmental Science and Pollution Research, 2022)

Correction to: Gyral-sulcal contrast in intrinsic functional brain networks across task performances - Lin Zhao; Tuo Zhang; Lei Guo; Tianming Liu; Xi Jiang (Brain Imaging and Behavior, 2021)

Trichome Lengths of the Heterocystous N2-Fixing Cyanobacteria in the Tropical Marginal Seas of the Western North Pacific - Sing-how Tuo; Margaret R. Mulholland; Yukiko Taniuchi; Houng-Yung Chen; Wann-Neng Jane; Yen-Huei Lin; Yuh-ling Lee Chen (Frontiers in Marine Science, 2021)
Calothrix rhizosoleniae and Richelia intracellularis are heterocystous cyanobacteria found in the tropical oceans. C. rhizosoleniae commonly live epiphytically on diatom genera Chaetoceros ( C-C ) and Bacteriastrum ( B-C ) while R. intracellularis live endosymbiotically within Rhizosolenia ( R-R ), Guinardia ( G-R ), and Hemiaulus ( H-R ); although, they occasionally live freely (FL- C and FL- R ). Both species have much shorter trichomes than the other marine filamentous cyanobacteria such as Trichodesmium spp. and Anabaena gerdii . We investigated the trichome lengths of C. rhizosoleniae and R. intracellularis in the South China Sea (SCS) and the Philippine Sea (PS) between 2006 and 2014. On average, H-R had the shortest trichome lengths (3.5 cells/trichome), followed by B-C and C-C (4.9–5.2 cells/trichome) and FL- C (5.9 cells/trichome), and R-R , G-R , and FL- R had the longest trichome lengths (7.4–8.3 cells/trichome). Field results showed the trichome lengths of C-C and B-C did not vary seasonally or regionally. However, FL- C and H-R from the SCS and during the cool season had longer trichomes, where/when the ambient nutrient concentrations were higher. R-R , G-R , and FL- R also showed regional and seasonal variations in trichome length. Ultrastructural analysis found no gas vesicles within the C. rhizosoleniae cells to assist in buoyancy regulation. Results suggest that the trichome lengths of C. rhizosoleniae and R. intracellularis might be regulated by their diatom hosts’ symbiotic styles and by ambient nutrients. Short trichome length might help C. rhizosoleniae and R. intracellularis to stay in the euphotic zone regardless as to whether they are free-living or symbiotic.

Gyral-sulcal contrast in intrinsic functional brain networks across task performances - Lin Zhao; Tuo Zhang; Lei Guo; Tianming Liu; Xi Jiang (Brain Imaging and Behavior, 2021)

Differences in Soil Microbial Community Composition Between Suppressive and Root Rot-Conducive in Tobacco Fields - Yaru Ding; Yulan Chen; Zhengquan Lin; Yangyang Tuo; Hongli Li; Yan Wang (Current Microbiology, 2021)

Cortical 3-hinges could serve as hubs in cortico-cortical connective network - Tuo Zhang; Xiao Li; Xi Jiang; Fangfei Ge; Shu Zhang; Lin Zhao; Huan Liu; Ying Huang; Xianqiao Wang; Jian Yang; Lei Guo; Xiaoping Hu; et al. (Brain Imaging and Behavior, 2020)
Mapping the relation between cortical convolution and structural/functional brain architectures could provide deep insights into the mechanisms of brain development, evolution and diseases. In our previous studies, we found a unique gyral folding pattern, termed a 3-hinge, which was defined as the conjunction of three gyral crests. The uniqueness of the 3-hinge was evidenced by its thicker cortex and stronger fiber connections than other gyral regions. However, the role that 3-hinges play in cortico-cortical connective architecture remains unclear. To this end, we conducted MRI studies by constructing structural cortico-cortical connective networks based on a fine-granular cortical parcellation, the parcels of which were automatically labeled as 3-hinge, 2-hinge (ordinary gyrus) or sulcus. On human brains, 3-hinges possess significantly higher degrees, strengths and betweennesses than 2-hinges, suggesting that 3-hinges could serve more like hubs in the cortico-cortical connective network. This hypothesis gains supports from human functional network analyses, in which 3-hinges are involved in more global functional networks than ordinary gyri. In addition, 3-hinges could serve as ‘connector’ hubs rather than ‘provincial’ hubs and they account for a dominant proportion of nodes in the high-level ‘backbone’ of the network. These structural results are reproduced on chimpanzee and macaque brains, while the roles of 3-hinges as hubs become more pronounced in higher order primates. Our new findings could provide a new window to the relation between cortical convolution, anatomical connection and brain function.

Novel dammarane-type saponins from Gynostemma pentaphyllum and their neuroprotective effect - Shao-Fang Xing; Man Lin; Yu-Rong Wang; Tuo Chang; Wei-Ye Cui; Xiang-Lan Piao (Natural Product Research, 2020)

Morphological and molecular diagnoses of Polydora brevipalpa Zachs, 1933 (Annelida: Spionidae) from the shellfish along the coast of China - Lingtong Ye; Tuo Yao; Lin Wu; Jie Lu; Jiangyong Wang (Journal of Oceanology and Limnology, 2019)

Impact of short-term climate variation and hydrology change on thermal structure and water quality of a canyon-shaped, stratified reservoir - Wei-Xing Ma; Ting-Lin Huang; Xuan Li; Hai-Han Zhang; Tuo Ju (Environmental Science and Pollution Research, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Subcellular localization of DAXX influence ox-LDL induced apoptosis in macrophages - Guozuo Xiong; Lin Li; Shaowei Sun; Tianping Li; Duanfang Liao; Chang Shu; Qinhui Tuo (Molecular Biology Reports, 2014)

Ferulic acid increases pain threshold and ameliorates depression-like behaviors in reserpine-treated mice: behavioral and neurobiological analyses - Ying Xu; Lu Zhang; Tuo Shao; Lina Ruan; Lin Wang; Jiao Sun; Jianxin Li; Xinbo Zhu; James M. O’Donnell; Jianchun Pan (Metabolic Brain Disease, 2013)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Three-dimensional interpretation of sparse survey line MT data: Synthetic examples - Chang-Hong Lin; Han-Dong Tan; Qing Shu; Tuo Tong; Yu-Mei Zhang (Applied Geophysics, 2012)

Three-dimensional conjugate gradient inversion of magnetotelluric impedance tensor data - Changhong Lin; Handong Tan; Tuo Tong (Journal of Earth Science, 2011)

Three-dimensional conjugate gradient inversion of magnetotelluric full information data - Chang-Hong Lin; Han-Dong Tan; Tuo Tong (Applied Geophysics, 2011)

Parallel rapid relaxation inversion of 3D magnetotelluric data - Changhong Lin; Handong Tan; Tuo Tong (Applied Geophysics, 2009)

Three-dimensional conjugate gradient inversion of magnetotelluric sounding data - Changhong Lin; Handong Tan; Tuo Tong (Applied Geophysics, 2008)

The parallel 3D magnetotelluric forward modeling algorithm - Tan Handong; Tong Tuo; Lin Changhong (Applied Geophysics, 2006)